Analisis Penggunaan Rasio Aset Dengan Metode Fixed Assets Turnover Ratio (FATO) Dan Total Assets Turnover Ratio (TATO) Dalam Laporan Keuangan PT. Bank Mandiri (Persero) Tbk - Holisatul Amalia; Krisna Reswara; Ika Murni Wati; Renny Oktafia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Banks are bodies or institutions that receive credit or loans. In banking finance we need to measure the asset ratio. Asset Ratio is the management of company assets in generating income which is used to evaluate the efficiency of financial management. The Asset Ratio includes a comparison between the company's total assets and the resulting income or net profit. Is the bank efficient in utilizing or using its fixed assets? One method for calculating a bank's asset ratio is the FixediAssets Turnover Ratioi (FATO) and Total AssetsiTurnover Ratio (TATO). Calculating these two analysis methods requires or involves all assets owned by the bank. a bank. In banking, the Fixed AssetsiTurnover Ratio (FATO) is a ratio that measures the effectiveness of a company in using its fixed assetiinvestments toigenerate net sales (services). Total Asset Turnover Ratio (TATO) is usually used to determine how effective a company's total assets are in generating income. From the results of the analysis of the financialistatements of PT. Bank Mandiri (Persero) Tbk in 2017-2021 can be concluded that the Company's activity ratio is still categorized as unfavorable. This is because the measurement of Fixed AssetiTurnover Ratio (FATO) and Total AssetsiTurnover Ratio (TATO) each year experiences fluctuations or is unstable or inefficient in managing fixed assets and total assets in supporting the Company's operations to generate income.